Gruzini i Ormianie we wspomnieniach Polaków zesłanych na Kaukaz w pierwszej połowie XIX wieku - Chrostek, Mariusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
Poles exiled to the Caucasus in the first half of the 19 th century were fond of Georgians. Kazimierz Lapczynski, Michał Butowt-Andrzejkowicz, Hipolit Jaworski, Jan Załęski and Ksawery Pietraszkiewicz described the picturesque dress and beauty and temperament of Georgian women and men. They praised them for their sincerity, hospitality and cheerful disposition. They also approved of their vices: drunkenness, laziness, endless late-night partying – they treated them as an important part of their nationality. Zygmunt Rewkowski spoke out critically – he rebuked immorality in Georgians, marital infidelity, young women's abuse of cosmetics and a gross lack of hygiene. In his memoir, Matthew Gralewski revealed the mechanisms of mass Russification of wealthy Georgians, who went into debt to Prince Mikhail Vorontsov's fund and mindlessly imitated the lifestyle of Russians. The simple Georgian people lived very poorly – peasants with their families and animals lived in pits dug in the ground. Along with Georgians, Armenians were among the most numerous peoples in the Caucasus. They mastered trade and craft and got rich quickly, so Georgians were often in debt to them, which is why they hated Armenians. This resentment was also shared by some Polish exiles, who, like Rewkowski and Lapczynski, spoke very unfavorably about Armenians. Matthew Gralewski and Hippolyte Jaworski rated the Armenians more fairly – they praised them for their diligence and modesty. Both Georgians and Armenians are depicted in everyday situations. Polish memoirists show them as friends, neighbors and acquaintances – they do not create them as heroes of the then fashionable Orient.
Georgians and Armenians in the memories of Poles exiled to the Caucasus in the first half of the 19 th century
Keywords: Georgians; Armenians; Polish exiles in the Caucasus; Poles in the tsarist army; Gralewski Mateusz; Rewkowski Zygmunt; Butowt-Andrzejkowicz Michał; Jaworski Hipolit; Łapczyński Kazimierz